Carcinomas mamários caninos: aspectos patológicos e imunofenotípicos do tumor primário e metástases linfonodais e seu impacto na sobrevida - Marina Rios de Araújo Campos (2015)
The present work aimed to determine the prognosis role of immunohistochemical expression of Her-2, Egfr, Cox-2 and Ki67 and the characteristics morphopathological (size of metastases, number of lymph nodes affected and of metastatic foci and presence of extracapsular extension) in lymph nodes metastasis of canine mammary carcinomas. We selected 54 primary mammary carcinomas with lymph node metastasis (T1,2,3N1M0) and 29 primary mammary carcinomas without metastasis (T1,2,3N0M0). Lymph nodes metastasis were evaluated according to size [macrometastasis (>2cm), micrometastasis (between 0.2cm and 2cm) and isolated tumor cells (<0.2cm)], number of positive lymph nodes and of metastatic focus, and extracapsular extension. Immunohistochemistry was performed in primary tumors and lymph nodes metastasis for evaluation of the expression of Her-2, Egfr, Cox-2 and Ki67. Survival data were obtained from 78 dogs and the maximum follow-up period was 1370 days. The presence of lymph node metastasis, the involvement of more than one positive lymph node, the presence of extracapsular extension, macrometastases, areas of metastasis >20.11 mm² and metastatic diameter >7.32 mm showed a direct relationship with shorter overall survival. In the immunohistochemistry analysis of markers we found a concordance between the expression of Her-2, Cox-2 and Ki67 and discordance between Egfr expression in metastatic primary tumors and paired lymph node metastasis. However, a high expression of these markers in lymph node metastasis did not exhibit direct relationship with a poor prognosis. We may conclude that the measurement of regional lymph node metastasis of canine mammary carcinomas should aid in the prognostic evaluation of the animals. However, despite the direct relationship of Her-2, Cox-2 and Ki67 expression in primary tumors and paired metastases, this assessment does not seem to be directly related to prognosis of the animal.